IMPLEMENTASI PENDIDIKAN DEMOKRASI MELALUI PEMBELAJARAN PKn UNTUK MEMBENTUK WARGA NEGARA YANG BERTANGGUNG JAWAB (Studi Kasus Eksplanatoris di SMP Islam Fathia Kota Sukabumi) - Septiana, Tina (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2022)
This research is motivated by: (1) The decline in the Civics learning process which causes students to concentrate less in the teaching and learning process. (2). The tendency of educators who teach is limited to imparting knowledge without any change in students' attitudes and behavior. (3). The creativity of Citizenship Education learning models among junior high school teachers is still less active, creative and innovative. (4). There is a demand that democratic education through citizenship education be taught to include the development of civic intelligence, civic participation and civic responsibility. Based on this, researchers conducted research entitled "Implementation of Democratic Education through Civics Learning to Form Responsible Citizens" which was carried out at Fathia Islamic Middle School Sukabumi. The problems analyzed are: (1). Packaging democratic education through Citizenship Education learning at Fathia Sukabumi Islamic Middle School. (2). Getting used to democratic education and students' responsible attitudes in Fathia Sukabumi Islamic Middle School. (3). Methods that can be used in democratic education are through Citizenship Education Learning to realize students' responsible attitudes at Fathia Sukabumi Islamic Middle School. (4). Factors that support and hinder the process of democratic education are the efforts made by schools and school committees in getting used to democratic education through learning Citizenship Education to form responsible citizens This research is motivated by: (1) The decline in the Civics learning process which causes students to concentrate less in the teaching and learning process. (2). The tendency of educators who teach is limited to imparting knowledge without any change in students' attitudes and behavior. (3). The creativity of Citizenship Education learning models among junior high school teachers is still less active, creative and innovative. (4). There is a demand that democratic education through citizenship education be taught to include the development of civic intelligence, civic participation and civic responsibility. Based on this, researchers conducted research entitled "Implementation of Democratic Education through Civics Learning to Form Responsible Citizens" which was carried out at Fathia Islamic Middle School Sukabumi. The problems analyzed are: (1). Packaging democratic education through Citizenship Education learning at Fathia Sukabumi Islamic Middle School. (2). Getting used to democratic education and students' responsible attitudes in Fathia Sukabumi Islamic Middle School. (3). Methods that can be used in democratic education are through Citizenship Education Learning to realize students' responsible attitudes at Fathia Sukabumi Islamic Middle School. (4). Factors that support and hinder the process of democratic education are the efforts made by schools and school committees in getting used to democratic education through learning Citizenship Education to form responsible citizens.